Pengaruh Metode Pengeringan Terhadap Aktivitas Antioksidan Ekstrak Etanol - Endra Pujiastuti; Rahma Sani Saputri (Cendekia Journal of Pharmacy, 2019)
Drying is the most important step to keep the compound stability in simplicia and is very influential to produce good quality igredients in the antioxidant activity contained in the simplicia. Antioxidants are oxidation-free inhibitors of free radical reactions. Parijoto is one of the plants that have antioxidant compounds.This study aims to determine the effect of drying, concentration of antioxidant activity of parijoto (Medinilla speciosa Blume) fruit. The drying method used is direct sunlight drying, indirect sunlight and oven. The antioxidant activity of ethanol extract on drying method was determined by 2,2 diphenyl-1-picrylhidrazyl (DPPH) method which is free radical. The qualitative test DPPH showed that the higher levels of ethanol extract from the three drying methods further diminished the color of DPPH solution in ethanol.The result showed thet the drying method gave different effect to the antioxidant activity of parijoto fruit which is significant(p0,05). Drying methods wich have high antioxidant activity are given by drying using oven method with an IC50Â value 33,75Âµg/ml.